2015
DOI: 10.1177/0840470415598405
|View full text |Cite
|
Sign up to set email alerts
|

Back to the future

Abstract: Improving patient experience has emerged as an important healthcare policy priority across Canada. Tools and systems for monitoring patient experience metrics are becoming increasingly refined and standardized, and the trend toward greater accountability for improvements that are sustainable and affordable is well underway. For many healthcare professionals, this represents a renewed focus on core patient needs and priorities, following decades during which structural and technological changes have dominated h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 8 publications
0
2
0
1
Order By: Relevance
“…However, organizational and clinical research have demonstrated that patient experience influences clinical safety and quality, as well as financial performance. 7 …”
Section: Results: Conceptualizing Measuring and Valuing Patient Exper...mentioning
confidence: 99%
“…However, organizational and clinical research have demonstrated that patient experience influences clinical safety and quality, as well as financial performance. 7 …”
Section: Results: Conceptualizing Measuring and Valuing Patient Exper...mentioning
confidence: 99%
“…The evaluation of patient experience helps healthcare organizations extract actionable insights to improve healthcare quality [38], [39], [40], increase engagement with the patient and their healthcare provider [41], [42], improve care effectiveness, lower employee turnover, and enhance employee satisfaction [43], [44], [45], [46]. Studies have also shown that patient experience can impact critical nancial levels dependent on patient retention and medical malpractice claims [46], [47], [48].…”
Section: Research In Patient-centered Care and Patient Experience Imp...mentioning
confidence: 99%
“…Patient satisfaction will offer valuable and distinctive insights into daily medical care and is widely accepted as a freelance dimension of quality of care as a result of an analysis of patient satisfaction includes "internal" (inward-looking) aspects of hospital care, which regularly stay unrecorded, like communica tion, fellow feeling or interaction (2,(3)(4)(5). However, various studies and systematic reviews demonstrate a correlation between subjective patient perspective and clinical safety and effectiveness, and that they demonstrate that patient satisfaction reflects totally different dimensions of quality of care (3,(6)(7)(8)(9)(10)(11)(12). Thus, it comes as no surprise that the activity of patient satisfaction is usually used as a tool to enhance the quality of care (8,12).…”
Section: Introductionmentioning
confidence: 99%